Friendship Circles in Hadith: Reconstructing Prophetic Teachings for Contemporary Social Networks - Fahmi Andaluzi; Muhammad Alif (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This study examines how the jawāmiʿ al-kalim character of hadiths on companionship can be interpreted in relation to the contemporary concept of friendship circles. Rather than treating prophetic narrations on friendship as isolated moral instructions, this research approaches them as an interconnected corpus oriented toward a shared waḥdah al-ghāyah (unity of purpose). Employing a thematic method of hadith analysis, the study collects and examines narrations related to companionship from classical sources accessed through digital compilations such as Maktabah Shāmilah and Mausūʿah al-Ḥadīthiyyah. The analysis identifies seventeen hadiths that collectively articulate a patterned ethical framework for social relations. These narrations reveal several relational dimensions, including the definition and urgency of companionship, the vision and moral purpose of friendship, the ethical principles regulating interaction, and the positive and negative social consequences of association. The findings suggest that the concise formulations of hadith function as relational signifiers that structure the ideals and boundaries of social interaction. When read as a semantic network, these traditions construct a moral grammar of companionship that remains relevant for interpreting the dynamics of contemporary friendship circles.